A sneaking epidemic the increasing overweight and obesity prevalence in the Philippines (1992-2018) - Henson, Bernice Gabrielle V. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
The Philippines faces an uphill battle against malnutrition and though the issues of stunting, wasting, and underweight are being addressed, evident by decreasing prevalence rates, overnutrition has been rising. The costs of overweight and obesity, be it loss of productivity or health costs, in the country has been estimated reach the equivalent to 567 million USD. It does not help the fact that National Nutrition Survey results reported overweight and obesity prevalence reporting to have risen from 5.8% in 2003 to 11.7% in 2018 in children ages >5-10 years old, for adolescents ages >10-19 years old it increased from 4.9% to 11.6%, and adults ages 20 and over has risen even more significantly, from 16.6% in 1991 to 37.2% in 2018. The obesity epidemic needs to be addressed sooner than later. This paper provides a look at the past 25 or so years on the topic of obesity and overweight in the country. The study uses data from DOST-FNRI's past National Nutrition Surveys up until the 2018 Expanded National Nutrition Survey, and both local and international related literature. Survey results show no signs of decreasing overweight and obesity prevalence rates in all age groups and has spiked notably in the years 2015-2018. Increased overweight and obesity prevalence is associated with high amounts of physical inactivity in all age groups but especially in adolescents, consumption of foods high in sugar and fat, and a person's socioeconomic status and type of residence. As the country's economy grows, so will the burden of overnutrition and this paper can assist in giving people an understanding of the current landscape on overweight and obesity in the Philippines and the factors behind it.
Thesis (BS Economics) - - University of the Philippines Diliman
Keywords: Obesity -- Philippines